Chapter "Flex 2018" Cruise: an opportunity to assess phytoplankton chlorophyll fluorescence retrieval at different observative scales - Lai, Antonia (Proceedings e report, 2020)
The "FLEX 2018" cruise, organized by the CNR-ISMAR in frame of the ESA "FLEXSense Campaign 2018" and CMEMS project, provided a ground station for several bio-optical instruments that investigated the coastal waters of the Tyrrhenian Sea in June 2018. The field measurements were performed in time synergy with Sentinel 3A and Sentinel 3B satellites and HyPlant airborne imaging spectrometer. Active and passive fluorescence were investigated at different scales in coastal waters to support preparatory activities of the FLuorescence EXplorer (FLEX) satellite mission.